A condição adolescente em contexto de vulnerabilidade social: problematizando violações de direitos com estudantes de uma escola pública municipal de Feira de Santana/BA - Ferreira, Ana Rita Almeida (2020)
This research approach the repercussions of social inequalities on the access and violation of the rights of adolescents in public schools. It aims to understand the adolescent condition in a situation of social vulnerability and violation of rights, in the perception of students from the 8th and 9th grade classes of a municipal public school in Feira de Santana / Ba. It is a research with a qualitative approach, which used questionnaires, discussion groups and interviews to produce dialogues with 8th and 9th grade students as data production tools. It is theoretically based on Wolff (2018), Pacheco and Almeida (2015), Azambuja (2018), Moreira (2016), Dias (2015), Santos and Rodrigues (2018), Alencar and Borges (2015), Moreira and Salles (2015), Candau, (2012), Nogueira (2002), Bueno (2001), Goular, Sampaio and Nespoli (2006), Saviani (2008), Aries (1981), Maia (2018), Bock (2007), Dayrell (1996), Coutinho (2009), Crivelatti and Hofstatter (2006), Neto and Koller, (2014); Oro Tomio (2010), Costa (2015).The results showed that the rights to health, education, public safety, habitacion, culture and recreation are greatly affected by the lack of investment and government action, in addition to showing the emergence of psychological distress in adolescence, triggered by external charges for greater autonomy, responsibility and projection of future life and problems such as violence, psychological and financial issues, mainly for the low-income population.